Perspectives on the treatment of chronic phase and advanced phase CML and Philadelphia chromosome positive ALL - Schiffer, Charles A.; Hehlmann, Rüdiger; Larson, Richard A. (Leukemia, 2003)
Chronic myeloid leukaemia (CML) is a malignant disease of the bone marrow characterised by the presence of the Philadelphia (Ph) chromosome. About 20% of acute lymphoblastic leukaemia (ALL) patients also show this genetic abnormality. A new drug, imatinib (Glivec®, Novartis Pharma AG, Basel, Switzerland, and formerly STI571) is having a profound effect on the treatment and management of all stages of CML and Philadelphia chromosome positive (Ph+) ALL. New treatment algorithms are being developed. Should imatinib replace or be combined with existing therapies? To address this question, we review the pros and cons of therapy with interferon-α (IFN-α), allogeneic transplantation, autologous transplantation, imatinib, and in the case of Ph+ ALL, chemotherapy and experimental approaches. Conservative and aggressive treatments will be discussed and new molecular methods of monitoring cytogenetic response and their significance will also be reviewed.